2022
DOI: 10.12998/wjcc.v10.i20.6769
|View full text |Cite
|
Sign up to set email alerts
|

Drainage of pancreatic fluid collections in acute pancreatitis: A comprehensive overview

Abstract: Moderately severe and severe acute pancreatitis is characterized by local and systemic complications. Systemic complications predominate the early phase of acute pancreatitis while local complications are important in the late phase of the disease. Necrotic fluid collections represent the most important local complication. Drainage of these collections is indicated in the setting of infection, persistent or new onset organ failure, compressive or pressure symptoms, and intraabdominal hypertension. Percutaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 55 publications
0
3
0
1
Order By: Relevance
“…Our data show that both cohorts underwent a variety of endoscopic diagnostic and therapeutic procedures. Moreover, published literature describes the risk of late complications weeks after the intervention, specifically for peripancreatic fluid collections[ 58 , 59 ]. In our analysis, several procedures were also identified as 30-day readmission predictors in AP patients with APFC, including endoscopic retrograde cholangiography (no intervention), endoscopic dilation of the ampulla and biliary duct, and endoscopic stone removal from the biliary tract.…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that both cohorts underwent a variety of endoscopic diagnostic and therapeutic procedures. Moreover, published literature describes the risk of late complications weeks after the intervention, specifically for peripancreatic fluid collections[ 58 , 59 ]. In our analysis, several procedures were also identified as 30-day readmission predictors in AP patients with APFC, including endoscopic retrograde cholangiography (no intervention), endoscopic dilation of the ampulla and biliary duct, and endoscopic stone removal from the biliary tract.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is useful in specific cases such as pancreatic pseudocyst. Studies have shown that PCD can significantly reduce the inflammatory response, accelerate the recovery of normal CRP levels, and reduce the risk of multiple organ failure [26] and surgical debridement [27] . For severe AP patients, PFC can also reduce the treatment costs of patients [28] .…”
Section: The Main Methods Of Treating Acute Pancreatitismentioning
confidence: 99%
“…Відповідно до міжнародних лікувально-діаностичних протоколів ведення хворих на ГП, етапний підхід у лікування захворювання є патогенетично обгрунтованим. Загальновизнаною альтернативою традиційним оперативним втручанням є застосування мініінвазивних пункційних дренуючих втручань на першому етапі лікування, при цьому ефективність черезшкірних методик складає 18-53% [7,8]. Проведений аналіз результатів застосування мініінвазивних черезшкірних ехо-контрольованих оперативних втручань показав, що впровадження у хворих основної групи удосконалених нами методик розширило можливості їх використання, у тому числі при локалізації інфікованих локальних ускладнень за правим та центрально-правим типом та вірогідно підвищило їх ефективність по відношенню до групи порівняння на 41,8% (χ2=4,84, 95% ДІ 5,37-64,13, p=0,02).…”
Section: матеріали та методиunclassified